Frauen Bauen Stadt - Czaja, Wojciech; Schechtner, Katja (Basel : Birkhäuser Verlag GmbH, 2021)
Araghian, Leila ; Awerbuch, Genia ; Bardi, Lina Bo ; Burckhardt-Blum, Elsa ; Diller, Elizabeth ; Grafton Architects ; Griffin, Marion Mahony ; Hadid, Zaha ; Lari, Yasmeen ; Popelka, Anna ; Potrč, Marjetica ; Roebling, Emily Warren ; Sejima, Kazuyo ; Søholt, Helle ; Tillner, Silja ; Vahl, Laura ; Walala, Camille ; Wenyu, Lu ; Aste, Kathrin ; Czaja, Wojciech ; Feireiss, Kristin ; Fitz, Angelika ; Gaál, Kathrin ; Gautrand, Manuelle ; Hall, Jane ; Heindl, Gabu ; Hofstetter, Kurt ; Kail, Eva ; Leeb, Franziska ; Mueller, Baerbel ; Müller, Katharina ; Novotny, Maik ; Pepchinski, Mary ; Pollak, Sabine ; Potrč, Marjetica ; Riß, Sabina ; Schechtner, Katja ; Schneider, Ute ; Unger, Petra
boek